2015
DOI: 10.1038/ncomms7153
|View full text |Cite
|
Sign up to set email alerts
|

UCHL1 provides diagnostic and antimetastatic strategies due to its deubiquitinating effect on HIF-1α

Abstract: Hypoxia-inducible factor 1 (HIF-1) plays a role in tumour metastases; however, the genes that activate HIF-1 and subsequently promote metastases have yet to be identified. Here we show that Ubiquitin C-terminal hydrolase-L1 (UCHL1) abrogates the von Hippel–Lindau-mediated ubiquitination of HIF-1α, the regulatory subunit of HIF-1, and consequently promotes metastasis. The aberrant overexpression of UCHL1 facilitates distant tumour metastases in a HIF-1-dependent manner in murine models of pulmonary metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
198
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(220 citation statements)
references
References 37 publications
10
198
0
Order By: Relevance
“…During the initial phases of adhesion, UCHL1 accumulates at the motile edge of the cell membrane; co-localizes with FAK, p120-catenin, and vinculin; enhances the formation of focal adhesion; and promotes FAK activation [27]. Recent research has demonstrated that UCHL1 provides diagnostic and antimetastatic strategies due to its de-ubiquitinating effect on HIF-1α [28]. In MKN45 and BGC823 cells, UCHL1 may increase cell motility ability through activation of FAK by Akt or Erk1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…During the initial phases of adhesion, UCHL1 accumulates at the motile edge of the cell membrane; co-localizes with FAK, p120-catenin, and vinculin; enhances the formation of focal adhesion; and promotes FAK activation [27]. Recent research has demonstrated that UCHL1 provides diagnostic and antimetastatic strategies due to its de-ubiquitinating effect on HIF-1α [28]. In MKN45 and BGC823 cells, UCHL1 may increase cell motility ability through activation of FAK by Akt or Erk1/2 signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…UCHL1 also acts as a colorectal cancer oncogene via activation of the beta-catenin/TCF pathway through its deubiquitinating activity [20]. Recently, UCHL1 is reported to promote metastases as a deubiquitinating enzyme for HIF-1␣ [21]. On the other hand, promoter hypermethylation leading to silencing of UCHL1 has been reported in progression of prostate cancer [22], breast cancer [23], nasopharyngeal carcinoma [24], hepatocellular carcinoma and other digestive tumors [25].…”
Section: Verification Of Differentially Expressed Proteins By Rt-pcrmentioning
confidence: 96%
“…CypA has been shown to stimulate cell motility and invasion by binding to the adaptor protein CrkII and preventing it from switching to its inactive form (38). Another potentially important up-CANCER GENOMICS & PROTEOMICS 14: 103-118 (2017) 112 regulated protein identified in this study is Ubiquitin C-terminal hydrolase-L1 (UCHL1), which promotes metastasis by deubiquitinating hypoxia inducible factor (HIF-1α) (39). The expression levels of UCHL1 in lung and breast cancer patients are a strong negative prognostic factor (39).…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 93%
“…Another potentially important up-CANCER GENOMICS & PROTEOMICS 14: 103-118 (2017) 112 regulated protein identified in this study is Ubiquitin C-terminal hydrolase-L1 (UCHL1), which promotes metastasis by deubiquitinating hypoxia inducible factor (HIF-1α) (39). The expression levels of UCHL1 in lung and breast cancer patients are a strong negative prognostic factor (39). Lectin galactoside-binding soluble 3 binding protein (LGALS3BP) has been previously shown to be elevated in pleural effusions from MM patients (40) and, paradoxically, its effusion level is positively associated with survival (40).…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%